Metal Packaging and Food Quality - B. Mehta, Meena (Asian Journal of Chemistry, 2010)
Over the years with man's quest for newer technology and packaging material for a variety of food products has gained prime importance. The conventional methods of harvesting, processing and handling are gradually replaced by modern systems with improvised and sophisticated techniques. The natural fruits, vegetables and all the perishable food products must be stored and sold without spoilage. Amongst various packaging materials, metal plays an important role to meet the necessary conditions to protect food products from spoilage. In the present paper, role and importance of tin metal is evaluated with respect to safety, stability and consumers acceptance. The usage of tin metal and its interaction with the food products causing changes in the nutritional value of food is discussed. The results indicate that tin does not impart toxicity to canned fruits and vegetables.